The content scope of airline sustainability reporting according to the GRI standards: An assessment for Europe's five largest airline groups - Martin Rüger; Sven Ulrich Maertens (Administrative Sciences, 2023)
The aviation industry is facing pressure from stakeholders to transform towards greater sustainability. From a managerial and marketing perspective, not only the actual implementation and achievements of sustainability measures, but also their communication to stakeholders is likely to be crucial - and in many cases even legally required. This research evaluates the scope of sustainability and corporate social responsibility (CSR) reporting of Europe's five largest airline groups for or from the year 2019, just prior the COVID-19 crisis. For this, dedicated sustainability reports and non-financial statements of Air France-KLM, easyJet, International Airlines Group, Lufthansa Group and Ryanair are evaluated and compared in a qualitative content analysis, using the Standards of the Global Reporting Initiative (GRI) as reference categories. The results indicate that the sustainability publications differ by airline business model, as the two low-cost carriers report less content in non-financial statements only, without publishing any standalone sustainability reports. Independent of the business model, most airlines surprisingly neglect the economic dimension of sustainability. The airline sector could improve its sustainability marketing by reporting both their economic, environmental, and social impacts and achievements.
Keywords: 350; Air France-KLM; air transport; airline sustainability reporting; corporate social responsibility; easyJet; Global Reporting Initiative; IAG; Lufthansa; Ryanair